2003
DOI: 10.1177/1046878103255877
|View full text |Cite
|
Sign up to set email alerts
|

Business Simulation Games: The Hong Kong Experience

Abstract: This article describes the results of a survey of 93 final-year degree students concerning their views toward using Thavikulwat's DEAL: A Business Gaming Simulation. The focus is on students'perception of the usefulness of using computer simulation as a learning tool in a strategic management course. Certain comparison was made with other similar studies in Australia and the United States. Highlights of positive as well as much less possible comments from local students on business games were also stressed.Muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 10 publications
1
29
0
2
Order By: Relevance
“…The measurements were adapted from the works of Adobor and Daneshfar (2006) and Chang, Lee, Ng and Moon (2003). The questionnaire is divided into 5 sections.…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurements were adapted from the works of Adobor and Daneshfar (2006) and Chang, Lee, Ng and Moon (2003). The questionnaire is divided into 5 sections.…”
Section: Measurementsmentioning
confidence: 99%
“…In UK, Burgess (1991) reported that 92% of business and management departments in polytechnics and 48.9% of UK universities were using business simulation games. However, the application of this teaching method in higher education in Asia is still limited (Du-Babcock & Babcock, 2002;Chang, Lee, Ng & Moon, 2003). The scenario is changing for the past 20 years; substantial accelerated growth is expected in this region.…”
Section: Introductionmentioning
confidence: 99%
“…UTM students) agreed that the usage of this system was enjoyable, apart from making time pass quickly. This was also seen in Chang et al (2003), whereby half of the respondents reported that the business game was interesting. This study has proven that there was another important element (other than perceived usefulness and attitude to use) that influenced the behavioral intention to use.…”
Section: Ro5: To Investigate the Relationship Between Perceived Enjoymentioning
confidence: 68%
“…Therefore, it is related to perceived enjoyment, whose concept is that an activity is enjoyable in its own right (Lee et al, 2005). This factor was included in studies like Chang et al (2003) and Tao et al (2009), whereby fun and interest were some of the elements that have been evaluated. Other than these two studies, Wawer et al (2010) stated that simulation games could be considered to be one of the most interesting forms of education.…”
Section: Perceived Enjoymentmentioning
confidence: 99%
“…Finally, serious gaming and assessment is another multimedia influenced topic of research. For example, researchers and practitioners have designed and tested virtual manager games to assess test takers competencies (Chang, Lee, Ng, & Moon, 2003).…”
Section: Research On Innovations In Assessmentmentioning
confidence: 99%